Thesis writing a practical guide - Leveriza, Jose P. (Quezon City New Day Publishers, 1997)
Purpose: "This book is an attempt to make thesis writing simple and easy. A compact and handy manual, graduate students may avail of the guidelines on how to write a thesis."
Contents: Parts of a thesis. Styles and concepts of writing. Information requirements. Making the manuscript. Completion of the thesis. Bibliography. Index. Other reference books from new day.
Keywords: Dissertations, Academic; Dissertations, Academic -- Handbooks, manuals, etc